Specificity of Government Financing Decisions and their Reflection in Financial Performance / Case Study in Diyala Governorate Sewerage Directorate - سعيد عبد السلام لفتة; عبد الامير محمد عبد المجيد (Journal of Economics and Administrative Sciences, 2020)
The aim of this research is to study the extent of the impact of government funding decisions on the financial performance of the directorate of Diyala province. The research problem was based on the financial reality of the directorate, and the data were collected from the financial divisions, planning and follow-up, implementation, and engineers of the resident engineer departments. Demonstrate the impact of government funding decisions on financial performance. Using scientific methods in estimating their financial needs through the annual estimated budget. The use of financial analysis to assess the performance of the Directorate, for the purpose of assessing the financial situation of the Directorate of research. The research adopted financial analysis tools, a set of financial ratios, through which the funding decisions taken by the Directorate of Research will be evaluated, and during the five years between (2014-2018). The research also relied on statistical methods such as the Pearson correlation coefficient, T-test, and simple linear regression. The research concludes with a number of results, the most important of which are: the correlation and influence relationships between financing decisions and financial performance differed; some have a significant relationship, while others do not exist. Lack of government allocations. Weakness in revenue from a service activity.